STRATEGI PENGEMBANGAN OBYEK WISATA BATIK KOTA PEKALONGAN - Ardhika Sukmasakti H; Banatul Hayati (Diponegoro Journal of Economics, 2013)
The Pekalongan city as a tourist attraction batik is quietly potential. Nevertheless, the number of tourist visits batik in Pekalongan likely decreasing from 2007 – 2010. This research aims to provide an overview of the development of batik tourism in Pekalongan and to analyze the development strategy batik tourism in Pekalongan. Using the AHP, this research identifies several aspects to investigate the Batik tourism development strategy including promotional, institutional, and infrastructure aspects. The result shows that among those three aspects, promotional aspect is chosen as the main aspect for the strategy. The result also shows that national and international batik festival are considered the most important strategy to attract more tourists to come. The batik festival can be increasing the number of tourist visits in Pekalongan.